Quantitative analysis of individual hepatocyte growth factor receptor clusters in influenza A virus infected human epithelial cells using localization microscopy - Wang, Qiaoyun; Dierkes, Rüdiger; Kaufmann, Rainer; Cremer, Christoph (Biochimica et biophysica acta. Biomembranes, 2014)
In this report, we applied a special localization microscopy technique (Spectral Precision Distance/Spatial Position Determination Microscopy/SPDM) to quantitatively analyze the effect of influenza A virus (IAV) infection on the spatial distribution of individual HGFR (Hepatocyte Growth Factor Receptor) proteins on the membrane of human epithelial cells at the single molecule resolution level. We applied this SPDM method to Alexa 488 labeled HGFR proteins with two different ligands. The ligands were either HGF (Hepatocyte Growth Factor), or IAV. In addition, the HGFR distribution in a control group of mock-incubated cells without any ligands was investigated. The spatial distribution of 1×106 individual HGFR proteins localized in large regions of interest on membranes of 240 cells was quantitatively analyzed and found to be highly non-random. Between 21% and 24% of the HGFR molecules were located in 44,304 small clusters with an average diameter of 54nm. The mean density of HGFR molecule signals per individual cluster was very similar in control cells, in cells with ligand only, and in IAV infected cells, independent of the incubation time. From the density of HGFR molecule signals in the clusters and the diameter of the clusters, the number of HGFR molecule signals per cluster was estimated to be in the range between 4 and 11 (means 5-6). This suggests that the membrane bound HGFR clusters form small molecular complexes with a maximum diameter of few tens of nm, composed of a relatively low number of HGFR molecules. This article is part of a Special Issue entitled: Viral Membrane Proteins — Channels for Cellular Networking.
Available online 27 December 2013
Gesehen am 25.08.2020